THE ROLE OF THE JURIST TODAY AND THE NECESITY OF RETHINKING HIS FORMATION - Loschiavo, Luca (2019)
This Work analyses the role of the jurist. First, addresses the reasons why the career of lawyer has lost appeal. Then analyses how the jurist was expelled of the “control room” of the State, reducing his role to an external technical consultant. Finally, contrasts the jurist as a technician that predominated after the second half of the XX century (logic in which the Law becomes, more than a system of counterweights, an instrument to legitimize strength positions), with the jurist as an intellectual, capable of reading the social changes and proposing solutions that contribute to the construction and support of the civitas. At last, proposes different strategies for the formation of that type of jurist, instead of the simple technician.